The gut microbiota is essential for Trichinella spiralis-evoked suppression of colitis. - Hualei Sun; Shao Rong Long; Miao Jiang; Hui Ran Zhang; Jing Jing Wang; Zi Xuan Liao; Jing Cui; Zhong Quan Wang (Public Library of Science (PLoS), 2024)
Background Inflammatory bowel disease (IBD) increases the risk of colorectal cancer, and it has the potential to diminish the quality of life. Clinical and experimental evidence demonstrate protective aspects of parasitic helminth infection against IBD. However, studies on the inhibition of inflammation by helminth infection have overlooked a key determinant of health: the gut microbiota. Although infection with helminths induces alterations in the host microbiota composition, the potential influence and mechanism of helminth infections induced changes in the gut microbiota on the development of IBD has not yet been elucidated. In this study, we analyzed the intersection of helminth Trichinella spiralis and gut bacteria in the regulation of colitis and related mechanisms. Methodology/principal findings T. spiralis infected mice were treated with antibiotics or cohoused with wild type mice, then challenged with dextran sodium sulfate (DSS)-colitis and disease severity, immune responses and goblet cells assessed. Gut bacteria composition was assessed by 16S rRNA sequencing and short-chain fatty acids (SCFAs) were measured. We found that protection against disease by infection with T. spiralis was abrogated by antibiotic treatment, and cohousing with T. spiralis- infected mice suppressed DSS-colitis in wild type mice. Bacterial community profiling revealed an increase in the abundance of the bacterial genus Muribaculum and unclassified_Muribaculaceae in mice with T. spiralis infection or mice cohoused with T. spiralis- infected mice. Metabolomic analysis demonstrated significantly increased propionic acid in feces from T. spiralis- infected mice. Data also showed that the gut microbiome modulated by T. spiralis exhibited enhanced goblet cell differentiation and elevated IL-10 levels in mice. Conclusions These findings identify the gut microbiome as a critical component of the anti- colitic effect of T. spiralis and gives beneficial insights into the processes by which helminth alleviates colitis.